Bet-hedging in innate and adaptive immune systems. Issue 1 (24th May 2022) - Tate, Ann T; Van Cleve, Jeremy
Abstract: Immune system evolution is shaped by the fitness costs and trade-offs associated with mounting an immune response. Costs that arise mainly as a function of the magnitude of investment, including energetic and immunopathological costs, are well-represented in studies of immune system evolution. Less well considered, however, are the costs of immune cell plasticity and specialization. Hosts in nature encounter a large diversity of microbes and parasites that require different and sometimes conflicting immune mechanisms for defense, but it takes precious time to recognize and correctly integrate signals for an effective polarized response. In this perspective, we propose that bet-hedging can be a viable alternative to plasticity in immune cell effector function, discuss conditions under which bet-hedging is likely to be an advantageous strategy for different arms of the immune system, and present cases from both innate and adaptive immune systems that suggest bet-hedging at play. Lay Summary: Organismal immune systems must contend with an onslaught of viruses, bacteria, and other parasites. Given the uncertainty of infection and the diversity of infectious organisms, the type of immune response, and to the extent that the immune system anticipates infection, can be beneficial or detrimental to host fitness depending on the context. In this perspective, we discuss the limits of these immune response types, and suggest that one overlooked but particularly important one — bet-hedging — may explain patterns of variation among cells of the innate and adaptive immune systems.